Process of nurse-patient interaction in the presence of technology - Alliex, Selma (Curtin University, 1998)
The purpose of this study was to develop a substantive theory or at least a set of theoretical propositions explaining the process of nurse-patient interaction in the presence of technology. This study was undertaken in Perth, Western Australia. The grounded theory method was chosen to undertake this research.The study's informants consisted of nurses. Theoretical sampling led to the inclusion of patients and patients' relatives. Purposive and theoretical sampling were used to choose the informants. Data were obtained using field observations and formal and informal interviews with nurses and post-discharge patients. Data analysis was conducted using the constant comparative method (Glaser and Strauss, 1967), writing memos and drawing a schema. The Ethnograph software package (Seidel, 1988) was used to organize and manage the data.The findings of the study indicated that nurses were stymied in their person-centered interactions with patients in the presence of technology. Nurses used the process of navigating the course of interaction to deal with this problem. The process of navigating the course of interaction consisted of three phases. These were the phases of embarking, steering and veering and disembarking. The action/interaction of the process occurred during the steering and veering phase and four specific strategies of interaction became evident in this research. These strategies of interaction were steadying, demurring, coasting and maximizing. The strategies of interaction used by nurses did not center on one type.There was rather a movement between strategies during and between interactions with patients in the presence of technology. This movement was termed oscillating connections. Conditions that modified the core process of navigating the course of interaction were also identified. The findings of the study provide an understanding of the problem encountered by nurses in their interaction with patients in the presence of technology and the process used by the nurses to deal with this problem.